(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
Diabetes are a disease that occurs in the blood, the division of sugar in the blood and the division of sugar in the urine and a disruption of all types of substance disorders. Diabetes diabetes are very common among the population